ASSESSMENT OF FACTORS AFFECTING ADHERENCE TO ANTIRETROVIRAL THERAPY AMONG HIV INFECTED ADOLESCENTS ATTENDING ART CLINIC AT KAJJANSI HEALTH CENTRE IV, WAKISO DISTRICT. A CROSS SECTIONAL STUDY. - Nantambi, Birungi Liz; Suubi, Mariam (Student’s Journal of Health Research Africa, 2023)
Introduction: HIV/AIDS pandemic remains a serious public health challenge globally therefore for ART to work efficiently, adherence is very essential. The study assesses factors affecting adherence to ART among HIV-infected adolescents attending the ART clinic at Kajjansi Health Centre. Methodology: The study was cross-sectional and qualitative methods of data collection were used. Results: The sample size of the respondents was 120 HIV-positive adolescents aged between 10 to 19 years attending the ART clinic at Kajjansi Health Center IV, the majority being males 69 (57.5%) and having attained secondary education 52 (43.3%). The biggest proportion 98 (81.7%) had ever missed taking drugs for reasons like having side effects, feeling better, and forgetfulness. The majority 86 (71.7%) had disclosed to relatives about their HIV and 64 (53.3%) were in boarding school. The biggest percentage 61.7% (74) did not know about their caregivers’ HIV status and the majority 60 (50%) reported a good relationship with the health workers. Conclusion: The low level of adherence to ART among HIV-infected adolescents at Kajjansi Health Center IV was attributed to patient-related factors like forgetfulness, side effects of the drugs, discrimination of adolescents, and being in boarding school. Caregiver-related factors like staying with biological parents, forgetfulness, poverty, and the HIV status of the caregiver also were positively associated with ART adherence and furthermore, health worker-related factors like relationship with the clients, maintaining confidentiality, and inadequate staffing. Recommendations: Increasing sensitization on ART adherence, increasing support to HIV service providers through improved budget allocations, educating adolescents on ART and how to adhere to treatment, orienting clients to other public facilities within their catchment area, and use of reminders to take drugs and seeking medical advice from health workers not only when side effects arise but also when they feel better.